Recasting Human Vδ1 Lymphocytes in an Adaptive Role. Issue 6 (June 2018) - Davey, Martin S.; Willcox, Carrie R.; Baker, Alfie T.; Hunter, Stuart; Willcox, Benjamin E.
Abstract : γδ T cells are unconventional lymphocytes commonly described as 'innate-like' in function, which can respond in both a T cell receptor (TCR)-independent and also major histocompatibility complex (MHC)-unrestricted TCR-dependent manner. While the relative importance of TCR recognition had remained unclear, recent studies revealed that human Vδ1 T cells display unexpected parallels with adaptive αβ T cells. Vδ1 T cells undergo profound and highly focussed clonal expansion from an initially diverse and private TCR repertoire, most likely in response to specific immune challenges. Concomitantly, they differentiate from a Vδ1 T cell naïve (Tnaïve ) to a Vδ1 T cell effector (Teffector ) phenotype, marked by the downregulation of lymphoid homing receptors and upregulation of peripheral homing receptors and effector markers. This suggests that an adaptive paradigm applies to Vδ1 T cells, likely involving TCR-dependent but MHC-unrestricted responses to microbial and non-microbial challenges. Highlights: Vδ1 T cells are the predominant tissue-associated γδ T cell subset in humans, and can recognise signs of cellular dysregulation, including viral infection and transformation. They are often assumed to be innate-like effectors. The Vδ1 TCR repertoire is initially diverse, yet a few clonotypes typically expand heavily over time. Such expanded clonotypes are diverse in sequence both within and between individuals. Clonal expansion occurs concurrently with differentiation from Vδ1 Tnaïve to Vδ1 Teffector status, alongside a switch from lymphoid to peripheral homing receptors, and upregulation of cytotoxic pathways. This concurrent expansion and differentiation suggests an adaptive-like response, likely driven by diverse stimuli, including microbial pathogen infection.